Faktor-Faktor Yang Memengaruhi Keputusan Pembelian Remaja Pada Tissue Basah Dettol Di Kota Batam - Sapta Kristamus; Tiurniari Purba (Komunitas Dosen Indonesia, 2023)
The explosive growth of the Dettol brand in recent years is a clear testament to the product's widespread popularity. The corporate world is sweeter than ever as competition in the wet wipes market intensifies. Several brands of wet wipes are usually available. With a variety of existing problems that have not been completely resolved. The aim of this research is to be able to find out whether brand image, brand trust and product quality can influence adolescent purchasing decisions on wet tissue in Batam City. Quantitative methods are used to conduct descriptive investigations. A descriptive study in which the researcher focuses on one independent variable without drawing any relationship between them. Teenagers from Batam City who have bought or used Dettol wipes are the population of this study. Under these circumstances, precise population figures are not available. Since the total number of people in the study population is unknown, the lameshow formula was used to come up with a sample size of 100 respondents. Data analysis techniques were used through validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), t test and f test. The results of the study stated that there was a positive and significant partial and simultaneous relationship between brand image, brand trust and product quality on adolescent purchasing decisions on Dettol wet wipes in Batam City